PROJECT IDENTIFICATION AND SELECTION TO PRIORITIZE THE BEST ALTERNATIVE PROJECT - Dwiarso, Adhi Priyo; Siahaan, Uke Marius; Damayanti, Sylviana Maya (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
This study develops a project prioritization framework for a cement manufacturing company, integrating economic, social, technical, and environmental metrics, specifically Net Present Value (NPV), Social Return on Investment (SROI), Thermal Substitution Rate (TSR), and CO2 emissions. The research addresses a critical gap in project prioritization studies by combining traditional economic metrics with sustainability-focused indicators, essential for the cement industry’s transition toward alternative fuel adoption. Using data from three alternative fuel projects, which are Waste Tire Pyrolysis, Biochar, and RDF. The study employs Analytical Hierarchy Process (AHP) for determining weights, Weighted Scoring for evaluating projects, and Monte Carlo Simulation to account for uncertainty in decision-making and creating scoring table. The results showed that Waste Tire Pyrolysis Project was the most balanced alternative, with the best performances in the financial, social, and environmental dimensions. This underlines the critical importance of adopting multi-criteria decision-making frameworks in tackling complex challenges that industries face, especially in sectors where sustainability has become a core priority.  Keywords: Project Prioritization, Multi Criteria Decision Making, NPV, SROI, TSR, CO2 Emission